UNITED STATES FOREIGN POLICY TOWARDS JORDAN FROM THE POLITICAL AND SECURITY DIMENSIONS FROM 1990 TO 2017 - Alkhawaldeh, Ala; Hayajneh, Ayman (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
Foreign policy is an integral part of international relations. This study examines the United States (US) foreign policy towards Jordan from 1990 to 2017 since the period witnessed important regional and international political events that significantly impacted the US foreign policy. These events have the greatest impact on the development of relations between the two countries in terms of political and security aspects. The study looks at four political events and their impacts on Jordanian-American relations from the political and security aspects. Therefore, the objectives of this study are to examine the US foreign policy towards Jordan from the political and security aspects. This study adopted the qualitative approach. The primary data were collected from interviews while the secondary data were obtained from books, journals, theses, newspapers, seminar papers, articles and other documents. In this study, 16 respondents from political, economic and security experts in Jordan and the US were selected for semi-structured interviews. The study employed Thematic Analysis in analysing the data obtained. This study adopted the neo-realism theory as a theoretical framework. This study found that the US foreign policy recognizes Jordan as a close ally and considers its stability very important. The US foreign policy was seen slightly negative towards Jordan during the Iraqi War on Kuwait in 1990. However, the Wadi Araba peace treaty between Jordan and Israel in 1994 had promoted positive US foreign policy towards Jordan. This policy was slightly weakened in 2017 due to the transfer of the US Embassy to Jerusalem. Certain political events play an important role in the US foreign policy regarding security aid towards Jordan. The study found that the US foreign policy provides security support to Jordan to protect Israel, spread American ideology and fight against its enemy. This research also found that Jordan has a suitable location to defend Israel because the country is surrounded by important Arab countries. The US links its aids to Jordan due to political events. Accordingly, the study recommends the necessity for the Jordanian state to increase its influential economic alliances at the international level. In addition, Jordanian policy must be redrawn in line with international realities to pressure the US to make Jordan play an active role in the region and international arena. Jordan should better use its geographical location to achieve international cooperation and enhance Arab security as a barrier against Israel.